How Might Transformation Be Achieved? Intrapreneurial Means to Achieve Networked Learning Ends - Zidulka, Amy (Proceedings of the International Conference on Networked Learning, 2026)
Networked Learning (NL) scholars aim to radically shift teaching and learning practices through digital innovation, in order to foster greater student empowerment, more holistic learning, and further connection between the university and society. However, implementing this vision is challenging due to the emergent and context-dependent nature of NL environments, as well as the inherent change resistance of postsecondary institutions. In response, NL scholars have advocated for adoption of approaches informed by design and speculative methods, while acknowledging further research is needed to put NL theories into practice. This conceptual paper explores how the scholarship of intrapreneurship, entrepreneurship within an existing organization, could complement existing approaches to implementing NL initiatives. Intrapreneurship scholarship assumes that intrapreneurs will navigate resistance within complex organizational contexts so allocates attention to understanding forces of resistance and potential mitigation. Intrapreneurship theory differentiates between the logic of causation, which drives action that is goal-oriented and planned, and that of effectuation, which drives emergent and non-linear action, with effectuation being more effective in uncertain situations or for radical innovation. Five principles of effectuation are outlined: “bird in the hand” (start with what you have), affordable loss (risk only what you can lose at each stage), “lemonade” (leverage the unexpected), “crazy quilt” (let partners shape direction), and “pilot in the plane” (focus on controllable aspects). Preliminary analysis suggests compatibility between effectuation theories of intrapreneurship and design-based and speculative methods, with all emphasizing exploratory, iterative action embedded in social and material contexts. Moreover, this paper finds that intrapreneurship theory has potential to contribute to advancement of NL initiatives through offering: (1) Insights into how change occurs within the entangled, social, political and material spaces of organizations; (2) Context-dependent knowledge on issues of relevance to those advancing NL initiatives, including research specifically focused on digital intrapreneurship and on intrapreneurship in public institutions; and (3) Affirmation of NL’s insights and approaches, since intrapreneurship scholarship arrive at similar conclusions from different empirical traditions. This is a preliminary, exploratory paper that concludes with potential directions for future research.